Explanatory Research on Zakat Model for Enhancing Disabled Persons' Socio-Economic Quality of Life - Hariya Toni; Muhammad Hisyam Syafii; Khairuddin; Muhlasin; Rafdeadi; Reno Diqqi Alghazali (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Abstract Individuals with disabilities have multifaceted obstacles that restrict their socioeconomic engagement, especially in developing nations where poverty rates surpass 68% within this demographic. This study looks at how well a productive zakat intervention works to make life better for persons with disabilities in Sungai Penuh City, Indonesia. The study employed a quasi-experimental design featuring pretest and posttest measurements, involving a registered population of 374 individuals with physical, auditory, and visual disabilities, from whom 35 participants met the purposive sampling criteria and underwent a three-month empowerment program comprising skills training, financial support for business ventures, social assistance, spiritual education, and continuous monitoring. The WHOQOL-BREF tool was used to measure quality of life in terms of physical health, mental health, social interactions, and the environment. Results indicated substantial enhancements in all domains, with an overall quality of life increase of 31.5% and effect sizes ranging from 1.45 to 2.17. The amount of money a household made went up by 121.6%, but the amount of debt they had went down by 52.9%. The results show that productive zakat is a transformative Islamic social finance tool that helps people who are economically disadvantaged while also encouraging psychological resilience, social reintegration, and more environmental options for people who are on the margins. Abstrak Penyandang disabilitas memiliki berbagai hambatan yang membatasi keterlibatan sosial ekonomi mereka, terutama di negara berkembang di mana angka kemiskinan melebihi 68% di kalangan demografis ini. Studi ini meneliti seberapa efektif intervensi zakat yang produktif dalam meningkatkan kualitas hidup penyandang disabilitas di Kota Sungai Penuh, Indonesia. Studi ini menggunakan desain kuasi-eksperimental yang menampilkan pengukuran pra-uji dan pasca-uji, melibatkan populasi terdaftar sebanyak 374 individu penyandang disabilitas fisik, pendengaran, dan penglihatan, di mana 35 peserta memenuhi kriteria pengambilan sampel bertujuan dan menjalani program pemberdayaan selama tiga bulan yang terdiri dari pelatihan keterampilan, dukungan keuangan untuk usaha bisnis, bantuan sosial, pendidikan spiritual, dan pemantauan berkelanjutan. Alat WHOQOL-BREF digunakan untuk mengukur kualitas hidup dalam hal kesehatan fisik, kesehatan mental, interaksi sosial, dan lingkungan. Hasil menunjukkan peningkatan yang signifikan di semua domain, dengan peningkatan kualitas hidup secara keseluruhan sebesar 31,5% dan ukuran efek berkisar antara 1,45 hingga 2,17. Jumlah uang yang dihasilkan rumah tangga meningkat sebesar 121,6%, tetapi jumlah utang mereka menurun sebesar 52,9%. Hasil penelitian menunjukkan bahwa zakat produktif adalah alat keuangan sosial Islami yang transformatif yang membantu orang-orang yang kurang mampu secara ekonomi sekaligus mendorong ketahanan psikologis, reintegrasi sosial, dan pilihan lingkungan yang lebih baik bagi orang-orang yang terpinggirkan.